The Potential of Art Development in the Present Era: A Case Study of the 'Nggusu Waru' Leadership Philosophy - Abdul Haris Rustaman; Damar Rangga Putra (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This investigation was motivated by the Eight Characteristics of Leadership in the Bima community called Nggusu Waru which means octagon, this can be seen in the shape of the Crown of the Bima Kingdom and lare-lare or the entrance gate to the Asi Mbojo Museum. This what inspired me, the Nggusu Waru form found in the Royal Crown shows 8 points of good leadership philosophy. On the one side, many Bimanesse people do not know about the Eight Characteristics of Nggusu Waru's leadership. A Bimanesse humanist and author of the book "Petuah Tanah Bima" whom I interviewed, Mr. Alan Malingi, said that currently what is happening in Bima society is almost not fulfilling towards Nggusu Waru, then our task is how to revitalize the values that exist in Nggusu Waru. I also observe that the trend of the current generation in using technology is very advance. The collaboration of the medium of art and technology can be an alternative to convey the meaning of Nggusu Waru's presence in the present era. The data collection process was carried out by interviews, field observations and literature studies. In general, the method I used was a qualitative method, then I classified the potential of new media from the point of view of art, and technology, and then determined the novelty . Thus, what I hope from this writing is to be able to provide an overview of the potential meaning of Ma Nggusu Waru in the present era with the collaboration of art and technology collaboration so that it can become a medium for contemplating the philosophy of Ma Nggusu Waru's leadership